Medicine as culture illness, disease and the body in Western societies - Lupton, Deborah 1963- (SAGE Publ., 1994)
Medicine as Culture provides a broad overview of the way medicine is experienced, perceived and socially constructed in Western societies. Deborah Lupton cogently links the different theoretical perspectives informing scholarship and research directed towards understanding the socio-cultural dimensions of medicine, illness and the body at the end of the twentieth century. At a time of increasing disillusionment with scientific medicine and the mythology of the beneficent, god-like physician, there is also - paradoxically - a growing dependence on biomedicine to provide the answers to social as well as medical problems. This book illuminates why attitudes to medicine are characterized by such strong paradoxes, and why issues of disease, illness and the medical encounter are surrounded by controversy, conflict, power struggles and emotion. Integrating cultural studies, social history and contemporary theories of the body, Medicine as Culture will be essential reading for students and academics in the sociology of health and illness, the sociology of consumption and everyday life, medical anthropology, the history of medicine, health communication, women's studies, nursing studies and cultural studies.
Keywords: Anthropologie médicale; Culturele aspecten; Geneeskunde; Médecine sociale; Kultur; Medizin; Anthropology, Cultural; Medical anthropology; Social Medicine; Social medicine; Kulturanthropologie; Medizinsoziologie; Aufsatzsammlung